Penerapan K-Means Clustering dalam Pengelompokan Data (Studi Kasus Profil Mahasiswa Matematika FMIPA UNM) - Zaki, Ahmad; Irwan; Sembe, Imanuel Agung (Jurusan Matematika FMIPA UNM, 2022)
This research is an applied research that aims to find out the clusters that exist in students of the Mathematics Department of FMIPA UNM using K-Means Clustering. This research method is a literature study. The results of the study obtained 4 clusters where the duration of independent learning and GPA from highest to lowest were Cluster 1, Cluster 2, Cluster 4, and Cluster 3. Cluster 1 was dominated by SBMPTN students, Semester 3, average age 19.20 years, duration of self-study 2.49 hours, 23.97 credits, 3.69 IPS, and 3.67 GPA. Cluster 2 is dominated by SBMPTN students, Semester 1, average age 18.08 years, duration of independent study 2.07 hours, 22 credits, 3.64 IPS and GPA 3.63. Cluster 4 is dominated by MANDIRI students, Semester 5, average age 19.78 years, duration of independent study 1.89 hours, 21.62 credits, 3.48 IPS, and 3.36 GPA. Cluster 3 is dominated by SBMPTN and SNMPTN students together, Semester 3, average age 18.52 years, duration of independent study 1.29 hours, 21.87 credits, 3.13 IPS, and GPA 3.19. The most influential variables in the formation of clusters are Semester, Number of Credits, GPA, Age, Social Studies, Average Duration of Independent Study, and Entry Path